An assessment of supply-side and demand-side policies in EU-28 household electricty prices - García-Álvarez, María Teresa (International Journal of Sustainable Energy Planning and Management, 2022)
An increase in household electricity prices has been taken place in the European Union in last years, which has been strongly influenced by the regulation component. This paper focuses on an empirical assessment of both supply-side and demand-side policies in the European Union over the period 2000-2015. More specifically, the analysis of the electricity industry liberalisation process and renewable energy support policies (from supply-side), as well as, energy taxes (from demand-side) has been developed in order to contribute to the present debate about the effect of these factors on household electricity prices. The results suggest that the liberalisation process has involved greater household electricity prices. Regarding solar photovoltaic energy support policies, the costs of quota obligation systems seem also to result in greater household electricity prices. However, energy taxes do not have a significant influence on these prices. Based on these results, recommendation actions are proposed for policy-makers.